Answer:
-19 y^2 + 18 x y + 13 x^2
Step-by-step explanation:
Simplify the following:
16 x^2 + 15 x y - 19 y^2 - (3 x^2 - 3 x y)
Factor 3 x out of 3 x^2 - 3 x y:
16 x^2 + 15 x y - 19 y^2 - 3 x (x - y)
-3 x (x - y) = 3 x y - 3 x^2:
16 x^2 + 15 x y - 19 y^2 + 3 x y - 3 x^2
Grouping like terms, 16 x^2 + 15 x y - 19 y^2 - 3 x^2 + 3 x y = -19 y^2 + (15 x y + 3 x y) + (16 x^2 - 3 x^2):
-19 y^2 + (15 x y + 3 x y) + (16 x^2 - 3 x^2)
x y 15 + x y 3 = 18 x y:
-19 y^2 + 18 x y + (16 x^2 - 3 x^2)
16 x^2 - 3 x^2 = 13 x^2:
Answer: -19 y^2 + 18 x y + 13 x^2
To calculate the tax multiply $860 by .06 (6%) to get $34.40.
To calculate the total amount you'll pay add $34.40 to $860 to get $894.40.
Answer:
C) (5,0)
Step-by-step explanation:
1. The correct answer is C) because when we move five units to right from the origin, and zero units up, we end up at point H!
Answer:
6+7=13
13+8=21
32+21=52
11+34=46
31+03=34
Step-by-step explanation:
im not sure in the 31+03
Answer:
150 m/s
Step-by-step explanation: